THE CONTROVERSY OF MUSLIM WORSHIP IN POST-PANDEMIC - Henky Fernando; Yuniar Galuh Larasati; Zaenuddin Hudi Prasojo (Penamas, 2023)
After the Covid-19 pandemic, the worship activities of Muslims have given rise to various controversies in the context of their principles, attitudes, and worship relations. In addition to explaining the controversies of Muslim worship after the Covid-19 pandemic, this study also analyzes the factors and implications of this phenomenon. This study uses a qualitative descriptive approach. Data was collected through direct observation and interviews with Muslims who carried out the five-time obligatory worship activities in the congregation at the mosque after the Covid-19 pandemic. The analysis in this study was carried out by reducing, describing, and inductively interpreting the data. The findings in this study show that post-Covid-19 pandemic worship controversies have not only appeared in the form of regulations, fqih, and worship norms. This context is influenced by the experience, knowledge, and meaning of Muslims, which has implications for the principles, attitudes, and patterns of worship in a more personal and subjective direction after the Covid-19 pandemic.